Plagiarism vs Similarity Index: A Critical Insight - Sandesh Narayan Somnache (German Journal of Pharmaceuticals and Biomaterials, 2023)
The word Plagiarism is derived from the Latin term "plagiarius", meaning "kidnapper" [1]. Plagiarism severely violates publication ethics and professional conduct [2]. It may be defined as an unethical intentional or unintentional piracy of someone else idea/s or text without acknowledgement [1]. Intentional Plagiarism usually occurs when some educational credentials, professional promotions, or economic benefits might benefit the concerned author(s)-unintentional plagiarism results either from negligence or lack of awareness about plagiarism [3]. The first incidence of plagiarism was detected in the year 1979 in a scientific paper. A later number of papers were found to be plagiarised [4]. A report published in 2018 showed an increased number of retractions of scientific papers in the last two decades due to plagiarism [5]. The primary reason for the increase in plagiarism by the scientific community could be a mandatory requirement to publish for employment and promotions. In addition, lack of skill in scientific writing and stringent policies related to plagiarism [4]. The availability of advanced text formatting tools and free access to scientific information may also reason for increased cases of plagiarism [6]. In the early days, plagiarism detection was challenging for the publisher due to the unavailability of sophisticated screening technology for reviewing manuscripts against published hard copies of the articles. Advanced tools for detecting plagiarism, such as iThenticate (Crossref), Turnitin, Grammarly, and Dupli Checker, are available to compare manuscripts with published articles [3,4]. Recently, iParadigms has developed a plagiarism detection tool for individual authors to screen individual manuscripts against an extensive live database of scholarly literature [7].